Identification and sequence analysis of a dreb subfamily transcription factor involved in drought stress tolerance from rice - Hoi, Pham Xuan; Tu, Tran Tuan (Academia Journal of Biology, 2014)
DRE (dehydration responsive element)/CRT (C-repeat) is a cis-acting element that involves in gene expression responsive to abiotic stress in higher plants. To date, all well known DREBP transcription factors in Arabidopsis, rice, maize and other plants regulate gene expression in response to drought, high-salt and cold stresses by binding specifically to DRE/CRT. Using a target sequence of 50 nucleotides on Glutamate dehydrogenase-like protein (JRC2606) promoter containing the core sequence of DRE cis-acting element (A/GCCGAC) for yeast one-hybrid screening, we have identified two transcription factors: a completely homology of OsRAP2.4A gene and another is a new sequence. The new sequence contained an ORF (Open Reading Frame) of 1017-bp and 5’ non-coding area of 35-bp and 3’ non-coding area of 341-bp. The deduced amino acid sequence contains an AP2 domain and belongs to the subgroup A6 of DREB subfamily, temporarily named OsRAP2.4B. Sequence alignment showed that OsRap2.4B had homology with ZmDBF, a maize transcription factor involved in drought stress tolerance.